WEB-BASED FOOD SALES INFORMATION SYSTEM USING AGILE METHODS AT AMPERA SARI MINANG RESTAURANT - Rahmad Dana; Suhendro Busono (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to develop a web-based food sales information system designed to enhance operational efficiency and customer satisfaction in the culinary business sector. Method: The system was developed using a structured software engineering approach, employing modern web technologies such as HTML, CSS, and JavaScript for the frontend, PHP or Python for the backend, and MySQL as the database management system. The development process included stages of system design, implementation, and testing to ensure functionality and usability. Results: The implementation results indicate that the system effectively streamlines business operations by reducing transaction processing time, improving data accuracy, enabling real-time stock monitoring, and facilitating easier access to information for both sellers and customers. Additionally, the integration of digital payment features enhances transaction convenience and minimizes manual errors. Novelty: The novelty of this research lies in the integration of a comprehensive management system—covering menu, orders, stock, and payments—into a single platform tailored for small and medium-sized culinary enterprises, thereby promoting digital transformation within the food service industry.